One new species and new record of the leafhopper genus Watara Dworakowska from Thailand (Hemiptera: Cicadellidae: Typhlocybinae: Erythroneurini) - Song, Yue-Hua; Gao, Ya-Rong; Li, Can (Zootaxa, 2018)
Morphological characteristics for identification of the leafhopper genus Watara Dworakowska are described and a key to all known species is provided. One new species, Watara longiprocessa sp. n., is added and one previously described species recorded from Thailand for the first time, Watara cordata Zhang & Yang, 2011 rec. n., is illustrated.